New ways to take advantage from solar energy and produce hydrogen - Rey de Castro, Ana (2012)
A research group at the Israel Institute of Technology has outlined the use of Fe2O3 photoanodes to enhance the efficiency of photoelectrochemical cells. The improvement is based on the design of extremely thinsheets of Fe2O3, which allow for a more efficient transport of charge carriers, reducing the amount of them that are lost due to recombination. Fe2O3 was chosen as a photoanode material due to its high stability in water, its high light absorption efficiency, the fact that it is non toxic and its low cost. Photoelectrochemical cells are extremely important in order to electrolyse water, hence producing hydrogen,a green fuel.